Higher Loading of Gold Nanoparticles in PAD Mesenchymal-like Stromal Cells Leads to a Decreased Exocytosis - Jennifer Oberländer; Rafael Ayerbe; Joan Cabellos; Richard da Costa Marques; Bin Li; Nazende Günday-Türeli; Akif Emre Türeli; Racheli Ofir; Eliran Ish Shalom; Volker Mailänder (Cells, 2022)
Cell therapy is an important new method in medicine and is being used for the treatment of an increasing number of diseases. The challenge here is the precise tracking of cells in the body and their visualization. One method to visualize cells more easily with current methods is their labeling with nanoparticles before injection. However, for a safe and sufficient cell labeling, the nanoparticles need to remain in the cell and not be exocytosed. Here, we test a glucose-PEG-coated gold nanoparticle for the use of such a cell labeling. To this end, we investigated the nanoparticle exocytosis behavior from PLX-PAD cells, a cell type currently in clinical trials as a potential therapeutic agent. We showed that the amount of exocytosed gold from the cells was influenced by the uptake time and loading amount. This observation will facilitate the safe labeling of cells with nanoparticles in the future and contribute to stem cell therapy research.